ANALYSIS OF FINANCIAL RATIO TO CHANGES IN PROFIT ON REGISTERED MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE - Ruth Yuliana; Neni Marlina Br Purba (Institute of Computer Science (IOCS), 2022)
Changes in profit are used by stakeholders to determine the company's previous financial performance. high profit changes indicate that financial performance is good so that it helps investors in making decisions. The population was taken by pharmaceutical companies listed on the Indonesian stock exchange in the 2017-2021 period as many as 12 companies and getting a sample of 8 pharmaceutical companies. The program used in this study to process data using IBM SPSS 25. The results of this research test indicate that only the t-test of Net Profit Margin has a significant effect on changes in earnings, three other variables such as current ratio, DAR, GPM have no effect on changes in earnings. The results of the F test state that the independent variables Current ratio, Net Profit Margin, DAR, and GPM have a significant effect on the dependent variable of Profit Change. And the result of the coefficient of determination test is 0.205 which shows that as much as 20.5% of the independent variables make a fairly effective contribution to profit changes. While the remaining 80.5% is controlled by other factors listed in this study.